Summary: Effects of flavonoids on glutathione level, lipid peroxidation and cytochrome P450 CYP1A1 expression in human laryngeal carcinoma cell lines - Durgo, Ksenija (Array, 2007)
Flavonoids are phytochemicals exhibiting a wide range of biological activities, among which are antioxidant activity, the ability to modulate activity of several enzymes or cell receptors and possibility to interfere with essential biochemical pathways. Using human laryngeal carcinoma HEp2 cells and their drug-resistant CK2 subline, we examined the effect of five flavonoids, three structurally related flavons (quercetin, fisetin, and myricetin), one flavonol (luteolin) and one glycosilated flavanone (naringin) for: (i) their ability to inhibit mitochondrial dehydrogenases as an indicator of cytotoxic effect, (ii) their influence on glutathione level, (iii) antioxidant/prooxidant effects and influence on cell membrane permeability, and (iv) effect on expression of cytochrome CYP1A1.